Social identity theory and leader-member exchange: Individual, dyadic and situational factors affecting the relationship between leader-member exchange and job performance - Gregory Thrasher; Marcus Dickson; Benjamin Biermeier-Hanson; Anwar Najor-Durack (Organization Management Journal (OMJ), 2020)
Purpose - This study aims to integrate social identity and leader-member exchange (LMX) theory to investigate the processes and boundary conditions around LMX-performance relationships. Through the application of two leader-follower subsamples, the authors test three main objectives. What is the effect of multi-dimensional dyad value-congruence on LMX and how does congruence on these dimensions differentially influence leader and follower perceptions of LMX? In a subsample of followers including supervisor-rated performance, the authors develop a model that examines how individual values moderate the effect of dyad contact on supervisor-rated job performance mediated by follower LMX. Design/methodology/approach - The participants for this study include graduate and undergraduate social work students who were taking part in a one-year work placement within a social work organization as well as their immediate supervisors. Across a four-month period, participants filled out measures of their supervisor contact, work values and LMX. Supervisor-rated performance was also included. Findings– Findings from the dyadic subsample show that growth value congruence is a predictor of follower-rated LMX, with value congruence across all values having no effect on leader-rated LMX. Within a subsample of followers, findings suggest that follower-rated LMX mediates the relationship between dyad contact and supervisor-rated job performance, with individual work values moderating this effect. Originality/value - The current study offers several contributions to the literature on LMX and job performance. First, in this study's dyadic leader-follower sample, the authors extend propositions made by social identity theory around value congruence and LMX by offering support for a multi-dimensional and multi-target approach to questions of values and LMX. Second, within this study's larger non-dyadic sample, the authors offer insights into previous conflicting findings around dyad contact and LMX, by offering support for the indirect effect of dyad contact on supervisor-rated performance via LMX. Third, within this second sample, the authors also extend the literature on values and LMX to show that the process through which LMX influences job performance is dependent on follower values.
Keywords: 650; Performance; Leadership; Values; LMX; P-S fit